Effectiveness of Language-Sensitive Geography Teaching. Findings from an Intervention Study - Wey, Santina; Schubert, Jan Christoph (Journal of Geography Education, 2023)
The empirically proven correlation between subject-related knowledge and technical language suggests that technical language requirements need to be explicitly addressed in Geography education to access subject content for all students regardless of their socio-economic and spatial background. This paper presents findings on the effectiveness of language-sensitive Geography teaching based on a corresponding teaching intervention. Within the methodological framework of design-based research, research and development work were interlocked in a prepost-follow-up design with one experimental and one control group (n = 185). The central finding is that the experimental group benefits statistically significantly and with a medium effect from language-sensitive Geography instruction concerning acquiring subject-related knowledge and technical language.